A polymer/detergent formulation improves dsRNA penetration through the body wall and RNAi‐induced mortality in the soybean aphid Aphis glycines. Issue 7 (7th February 2019) - Zheng, Yang; Hu, Yiseng; Yan, Shuo; Zhou, Hang; Song, Dunlun; Yin, Meizhen; Shen, Jie
Abstract: BACKGROUND: It is difficult to efficiently silence gene expression in some insects, probably because of the degradation of dsRNA by enzymes present in the gut and hemolymph post‐oral feeding or body injecting of dsRNA. We previously developed a nanocarrier delivery system that can systemically deliver dsRNA into chewing mouthpart insects by oral feeding and efficiently silence gene expression. For the purpose of pest control in the field, there is a great demand to develop a spray method to apply dsRNA formulation. RESULTS: A formulation of the nanocarrier/dsRNA/detergent was developed and could be easily applied just by dropping it on the notum of the aphid. The formulation penetrated the body wall into the hemocoel and then spread into various tissues within 1 h. The delivered dsRNA efficiently silenced the target gene expression at a high knockdown effect (95.4%) and the aphid population was largely suppressed (80.5%). CONCLUSION: A novel dsRNA formulation was developed with the help of a nanocarrier and detergent that can quickly penetrate the insect body wall and efficiently silence gene expression. The formulation may provide a fast and easy tool for gene silence in some tough insects and for pest control in the field. © 2019 Society of Chemical Industry Abstract : A well‐developed fluorescent nanocarrier and detergent were introduced as the main components in our delivery system. The nanocarrier is a cationic dendrimer that consists of a fluorescent Perylene diimide core and four peripheral amino acid functionalized arms.